The segment as the minimal planning unit in speech production and reading aloud: evidence and implications - Kawamoto, Alan H.; Liu, Qiang; Kello, Christopher T. (Frontiers in Psychology, 2015)
Speech production and reading aloud studies have been treated as relatively distinct research enterprises for many years, but there has recently been increasing recognition that they have much in common, especially the last stages involved in producing a response. The issue that we focus on in this review is the minimal planning unit (MPU) in articulation. Many researchers once assumed that the MPU was the phonological word, although most researchers now assume that it is the syllable. However, there have also been a few researchers who have assumed that the MPU is smaller than the syllable. We present evidence based on absolute response latencies and initial segment durations in phonological priming and speeded naming studies that the MPU is at least as small as the segment, and discuss why such evidence was not found in earlier studies. Next, we rebut the argument that the segment MPU cannot account for anticipatory coarticulation. Finally, we argue that the segment MPU is important not only in its own right, but also because it provides an alternative explanation of results implicated in the serial vs. parallel processing debate.